Leachate characterisation and evaluation of leachate pollution potential of urban municipal landfill sites - Mishra S.; Tiwary D.; Ohri A. (My University, 2025)
Toxic materials from unorganised dumping site leached out in the form of leachate and pollute the groundwater that results in significant impacts on the human health and environment. Management of this highly toxic leachate is essential for assessing the impact of municipal solid waste (MSW) landfills to ensure least environmental impact. The aim of this study is to assess the leachate characteristics and pollution potential index (LPI) of two major MSW landfills of Varanasi, city namely Karsara and Ramna. Leachate samples were collected from Karsara and Ramna landfill sites and analysed for 27 leachate quality parameters. The concentration of contaminants present in leachate at Karsara landfill site is comparatively greater than that of Ramna landfill site which indicates that Karsara landfill site is more polluted than Ramna landfill site. Twelve most significant parameters like pH, TDS, BOD5, COD, arsenic, chloride, chromium, copper, iron lead, nickel, and zinc are considered to estimate the leachate pollution potential. Karsara landfill site was found the highest LPI value (16.81) as compared to Ramna landfill site (12.40). LPI value indicates that the leachate generated from both the landfill site is hazardous. Hence active post-closure monitoring is necessary till the leachate production is stabilised. Copyright © 2018 Inderscience Enterprises Ltd.